BUILDING FROM AND MOVING BEYOND THE STATE: The National and Transnational Dimensions of Afro-Brazilian Women's Intersectional Mobilization - Franklin, Jessica H. (My University, 2013)
Race and gender categories have rarely operated in isolation in the lives of Afro-Brazilian women, intersecting to shape their historical and social positioning, everyday experiences, and collective activism. Despite opposition from the Brazilian state and some civil society groups, the Afro-Brazilian women’s movement has increased awareness of the specificity of black women’s identities and oppressions. In recent years their activism has moved beyond Brazil’s borders through participation in United Nations (UN) Conferences. Yet, the dynamism of Afro-Brazilian women’s intersectional identities and their strategic use to gain legitimacy in these arenas has remained noticeably understudied.
This dissertation argues that since activist groups do not participate in transnational forums detached from their specific histories and localized experiences, their actions, and strategies must be historically grounded. It draws upon the major arguments of postcolonial feminism, intersectionality, and the political process model to examine how national and transnational processes have shaped the identity articulations and mobilization strategies of Afro-Brazilian women activists. Four distinct processes operating in and outside of Brazil are identified as critical to the identity positions, strategies, and overall trajectory of the Afro-Brazilian women’s movement: colonialism, slavery, democratic transition, and preparations for and proceedings of UN Conferences. The influence of Afro-Brazilian women activists in domestic policy domains and internal movement dynamics are also explored. The result is a comprehensive analysis of the intricate workings of race and gender categories in activist spaces and the multiple historical and contextual factors which shape their configuration, intersection, and impact.
Keywords: Race; Gender; Brazil; Transnationalism; Women; Activism; Feminist, Gender, and Sexuality Studies; Latin American Languages and Societies; Race, Ethnicity and post-Colonial Studies; Feminist, Gender, and Sexuality Studies